Analisis Sistem Informasi Akuntansi Penggajian Dalam Upaya Mendukung Pengambilan Keputusan Pada Rumah Sakit Umum Haji Medan - Dimas Sanjaya; Yenni Samri; Rahmat Daim Harahap (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Current economic developments have been encouragingcompany growth to enlarge and expand spacescope of business. Likewise, current information systems havemakes it easier for companies to deal with problems that may occur in the payroll process. Objective This research is to find out how the system is implemented payroll accounting at the Medan Haji General Hospital and for find out whether the payroll accounting system is implemented by Companies can help management in decision making towards salary. This type of research is a type of qualitative research with a descriptive approach that uses primary data such as results of interviews with the company and secondary parties such as structureorganization. Data collection techniques were carried out using techniques observation, interviews, and literature, data analysis methods used is a descriptive method. This research was conducted in Medan Haji General Hospital which is located on Jl. Hajj Hospital – Estate terrain and research time starts in January 2024 until the completion of this thesis. The results of this research show that the accounting system implemented by the Hajj General Hospital to handle payroll has been quite adequate in helping company management in making decisions regarding salaries, p This is good because the company employs employees from a wide range levels and in very large numbers and provide rewards for their services in the form of salaries, so the company must have effective accounting system.